COMPARISON OF MICRONIZED PROGESTERONE VERSUS NIFEDIPINE IN PREVENTION OF PRETERM LABOR. - Raishem Ali1 , Shahida Karamat2 , Saira Saeed3 , Areeba Jawaid4 , Samreen Kazmi5 , Naseem Mallah6 ., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: The definition of preterm labor is when a woman gives birth before completing 37 weeks of gestation, which is calculated from the last menstrual cycle date OBJECTIVE: To determine the effectiveness of micronized progesterone versus nifedipine in the prevention of preterm labor.METHODOLOGY: A randomized controlled trial was conducted by the Department of Obstetrics and Gynecology at Peoples University of Medical & Health Science for Women Nawabshah during the period of September 2019 to October 2020. Eighty-three women were treated with micronized progesterone (group 1) and 83 women were treated with nifedipine (group 2). Nifedipine tocolysis was initiated orally. Prior to administering the treatment, the blood pressure, pulse, uterine contractions and fetal heart rate of the mother were assessed. Documentation was conducted every thirty minutes within the initial hour and then hourly for up to four hours. Following this, documentation took place every four hours until a final outcome was reached at twelve hours. RESULTS: Mean age of group 1 and group 2 was 29.01 ± 5.59 years and 28.06 ± 6.18 years, respectively. The mean parity was 2 ± 0.73 in group 1 and 2 ± 0.64 in group 2. There were 39 (46.99%) primigravida and 44 (43.01%) multigravida in group 1 while 21 (25.30%) primigravida and 62 (74.70%) multigravida in group 2. Effectiveness was significantly high in group 1 as compared to group 2 (77.1% vs. 57.8%; p=0.008). CONCLUSION: It is concluded that treatment with micronized progesterone resulted in a substantial reduction in the rate of recurrent preterm delivery among women who were at particularly high risk for preterm delivery and reduced the likelihood of several complications in their infants.